2019
DOI: 10.1002/jcc.26096
|View full text |Cite
|
Sign up to set email alerts
|

Critical Assessment of the DFT + U Approach for the Prediction of Vanadium Dioxide Properties

Abstract: In a previous study (Stahl and Bredow, Chem. Phys. Lett. 2018, 695, 28–33), we have studied structural, energetic, and electronic properties of two vanadium dioxide VO2 polymorphs with modified global and range‐separated hybrid functionals. Since hybrid methods are computationally demanding, we evaluate the computationally more efficient DFT + U method in the present study. We assessed the widely used Dudarev PBE + U approach with a literature value of the effective Hubbard parameter Ueff = 3.4 eV. We compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 53 publications
4
45
0
Order By: Relevance
“…In a previous study [29] we found that a self‐consistent hybrid functional (sc‐PBE0) with 12.7 % Fock‐exchange provides accurate structural, energetic and electronic properties for both VO 2 phases in the bulk. Therefore, the sc‐PBE0 functional, as implemented the program CRYSTAL17 v1.0.2, [30] is used in this study to calculate surface properties.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study [29] we found that a self‐consistent hybrid functional (sc‐PBE0) with 12.7 % Fock‐exchange provides accurate structural, energetic and electronic properties for both VO 2 phases in the bulk. Therefore, the sc‐PBE0 functional, as implemented the program CRYSTAL17 v1.0.2, [30] is used in this study to calculate surface properties.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Therefore, the sc‐PBE0 functional, as implemented the program CRYSTAL17 v1.0.2, [30] is used in this study to calculate surface properties. Comparatively small basis sets with respect to the standard pob‐TZVP basis sets, [31] which were applied in our previous studies on VO 2 , [7,29] are used to reduce the computational effort. For Vanadium a modified 86‐411d31G basis set by Harrison et al [32] .…”
Section: Computational Detailsmentioning
confidence: 99%
“…The decrease of energy gaps was mainly originated from the down-shift and broadening of the conduction band. 61,65 According to PDOSs, the broadening is due to the decreasing locality of V 3d and O 2p constituting the conduction band with increasing hydrogen concentration from two hydrogen to five hydrogen atoms. When there are more than six hydrogen atoms, the conduction band levels are obviously divided into two groups, and the group near the Fermi level moves to the lower energy with the increase of hydrogen atoms from six to seven, resulting in the further decrease of the band gap (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…First‐principles calculations were performed using the DFT with the projector augmented wave method [ 47 ] and generalized gradient approximation of the Perdew–Burke–Ernzerhof functional [ 48 ] as implemented in the Vienna Ab initio Simulation Package. [ 49 ] Spin‐polarized calculations were performed and the effective Hubbard U correction (3.4 eV for V [ 50 ] ) was used for the GGA + U methods. [ 51 ] The vdW interactions were corrected using the Grimme method (DFT‐D3).…”
Section: Methodsmentioning
confidence: 99%